Literacy and augmentative and alternative communication - Smith, Martine (Augmentative and alternative communication perspectives series., 2005)
In order to read, individuals with severe speech impairments must access a set of written symbols and decode them to abstract meaning just as anyone else must do. They must convert underlying messages into an alternative external symbol format in order to write.